Bored Tuesdays and Focused Afternoons: The Rhythm of Attention and Online Activity in the Workplace - Mark, Gloria; Iqbal, Shamsi; Czerwinski, Mary; John, Paul (ACM Conference on Computer-Human Interaction, 2014)
While distractions due to digital media have received attention in HCI, we examine instead focused attention in the workplace. We logged digital activity and continually probed perspectives of 32 information workers for five days in situ to understand how attentional states change with context. We present a framework of how engagement and challenge in work relate to focus, bored, and rote work. Overall, we find more focused attention than boredom in the workplace. Reported focus peaks mid-afternoon while boredom is highest in the morning. People are happiest doing rote work; we show that focused work can involve stress. We identified higher levels of boredom mid-week. Online activities are associated with different attentional states, showing different patterns at beginning and end of day, and before and after a mid-day break. Our study shows how rhythms of attentional states are associated with context